Modular eigenforms at the boundary of weight space - Vonk, J (Springer Verlag, 2018)
Andreatta, Iovita, and Pilloni recently introduced Fp((t))-Banach spaces of overconvergent t-adic modular forms, whose weight may be considered a “boundary” point of weight space. In an effort to make them concrete and accessible to explicit experimentation, we construct orthonormal bases, deduce t-adic analogues of certain p-adic results in the literature, and exhibit explicit examples.